A Randomized, Double-Blind, Placebo-Controlled, Bridging Study to Evaluate the Efficacy and Safety of Vibegron in Treating Korean Patients With Overactive Bladder - Jung Hyun Shin; Seong Jin Jeong; Sun-Ouck Kim; Cheol Young Oh; Kyung Jin Chung; Dong Gil Shin; Tae Hyo Kim; Joonbeom Kwon; Ju-Hyun Shin; Woong Jin Bae; Kyu-Sung Lee; Myung-Soo Choo (International Neurourology Journal, 2023)
Purpose Vibegron, a novel, potent β3 agonist, has been approved for clinical use in overactive bladder (OAB) treatment in Japan and the Unites States. We performed a bridging study to investigate the efficacy and safety of a daily 50-mg vibegron (code name JLP-2002) dose in Korean patients with OAB. Methods A multicenter, randomized, double-blind, placebo-controlled study was conducted from September 2020 to August 2021. Adult patients with OAB with a symptom duration of more than 6 months entered a 2-week placebo run-in phase. Eligibility was assessed at the end of this phase and selected patients entered a double-blind treatment phase after 1:1 randomization to either the placebo or vibegron (50 mg) group. The study drug was administered once daily for 12 weeks and follow-up visits were scheduled at weeks 4, 8, and 12. The primary endpoint was the change in mean daily micturition at the end of treatment. The secondary endpoints included changes in OAB symptoms (daily micturition, nocturia, urgency, urgency incontinence, and incontinence episodes, and mean voided volume per micturition) and safety. A constrained longitudinal data model was used for statistical analysis. Results Patients who took daily vibegron had significant improvements over the placebo group in both primary and secondary endpoints, except for daily nocturia episodes. The proportions of patients with normalized micturition and resolution of urgency incontinence and incontinence episodes were significantly higher in vibegron group than in the placebo. Vibegron also improved the patients’ quality of life with higher satisfaction rates. The incidence of adverse events in the vibegron and placebo groups was similar with no serious, unexpected adverse drug reactions. No abnormality in electrocardiographs was observed as well as no significant increase in postvoid residual volume. Conclusions Once daily vibegron (50 mg) for 12 weeks was effective, safe, and well-tolerated in Korean patients with OAB.